CO2 utilization and sequestration potential in deep coal seams: A case study on Carboniferous coals from the Karaganda Basin, Kazakhstan - Majid Safaei-Farouji; David Misch; Reinhard F. Sachsenhofer; Nikolaos Kostoglou; Garri Gaus; Thorsten Bauersachs; Medet Junussov; Milovan Fustic (Journal of CO2 Utilization)
Kazakhstan is a major coal producer and emitter of carbon dioxide (CO2), presenting both a challenge and an opportunity for CO₂ utilization and storage. The main goal of this work is to study the feasibility of CO2 as a feedstock for enhanced coalbed methane recovery (CO2-ECBM), as well as the associated geological storage potential of the D6 coal seam in the Karaganda Basin. For this purpose, coal samples were investigated using elemental analysis, Rock-Eval pyrolysis (RE), organic petrography as well as low-pressure (LP: N2, CO2), and high-pressure (HP: CO2, CH4) sorption tests. Vitrinite reflectance values show that seam D6 reached the medium-volatile bituminous rank. Higher organic matter content significantly increases the LP CO2 sorption capacity. The adsorption-desorption isotherms of CO2 recorded under both LP and HP conditions show a hysteresis loop. This is probably due to interactions between CO2 and functional groups leading to enhanced physisorption at LP and chemisorption and matrix swelling at HP conditions. This effect is favorable for storage purposes as it implies safe CO2 trapping even at reduced reservoir pressure. The CBM potential of seam D6 is estimated at 9 billion m3 initial gas and 360 million m3 producible gas in place. Estimates of the adsorptive and total CO2 storage capacity yielded 1.1 and 3.6 gigatons (Gt), respectively. With this considerable total storage capacity, Kazakhstan's current annual CO2 emissions could be stored for 14 years. This study highlights how CO2 can be effectively utilized as a feedstock to enhance methane recovery while achieving long-term CO2 sequestration.